The Global Health Service Partnership: An Academic-Clinical Partnership to Build Nursing and Medical Capacity in Africa - Eileen M. Stuart-Shor; Eileen M. Stuart-Shor; Eileen M. Stuart-Shor; Elizabeth Cunningham; Laura Foradori; Elizabeth Hutchinson; Elizabeth Hutchinson; Martha Makwero; Jill Smith; Jane Kasozi; Esther M. Johnston; Esther M. Johnston; et al. (Frontiers Media S.A., 2017)
The World Health Organization estimates a global deficit of about 12.9 million skilled health professionals (midwives, nurses, and physicians) by 2035. These shortages limit the ability of countries, particularly resource-constrained countries, to deliver basic health care, to respond to emerging and more complex needs, and to teach, graduate, and retain their future health professionals-a vicious cycle that is perpetuated and has profound implications for health security. The Global Health Service Partnership (GHSP) is a unique collaboration between the Peace Corps, President's Emergency Plan for AIDS Relief, Seed and host-country institutions, which aims to strengthen the breadth and quality of medical and nursing education and care delivery in places with dire shortages of health professionals. Nurse and physician educators are seconded to host institutions to serve as visiting faculty alongside their local colleagues. They serve for 1 year with many staying longer. Educational and clinical best practices are shared, emphasis is placed on integration of theory and practice across the academic-clinical domains and the teaching and learning environment is expanded to include implementation science and dissemination of locally tailored and sustainable practice innovations. In the first 3 years (2013-2016) GHSP placed 97 nurse and physician educators in three countries (Malawi, Tanzania, and Uganda). These educators have taught 454 courses and workshops to 8,321 trainees, faculty members, and practicing health professionals across the curriculum and in myriad specialties. Mixed-methods evaluation included key stakeholder interviews with host institution faculty and students who indicate that the addition of GHSP enhanced clinical teaching (quality and breadth) resulting in improved clinical skills, confidence, and ability to connect theory to practice and critical thinking. The outputs and outcomes from four exemplars which focus on the translation of evidence to practice through implementation science are included. Findings from the first 3 years of GHSP suggest that an innovative, locally tailored and culturally appropriate multi-country academic-clinical partnership program that addresses national health priorities is feasible and generated new knowledge and best practices relevant to capacity building for nursing and medical education. This in turn has implications for improving the health of populations who suffer a disproportionate burden of global disease.